Perception of the use of cost system for supervision of municipalities by the TCE/SC (Revista Brasileira de Contabilidade e Gestão, 2013)
LRF requires system maintenance costs by the government. The Court of the State of Santa Catarina (TCE/SC) is responsible for supervising the municipalities of Santa Catarina. It investigates the perception of crowded servers in the order of the Municipal Board of Control on the use of cost system for monitoring the application of constitutional principles of efficiency and economy. The research is exploratory and approach is predominantly qualitative. We can see the division of opinions about what the system costs can be helpful in this inspection. We conclude that the subject is still new and needs time to mature.
Keywords: system costs; court of auditors; economy; efficiency